Effects of high concentrate rations on ruminal fermentation and microbiota of yaks - Pang, Kaiyue; Dai, Dongwen; Yang, Yingkui; Wang, Xun; Liu, Shujie; Huang, Weihua; Xue, Bin; Chai, Shatuo; Wang, ShuXiang (Frontiers in Microbiology, 2022)
Ruminal microflora is closely related to the ruminant's diet. Currently, there is less information about the effect of high concentrate diets on rumen microflora in yaks. In this study, 24 healthy male yaks were randomly assigned to two groups, each fed different diets: low concentrate diet (LC) (concentrate: coarse = 40:60) and high concentrate diet (HC) (concentrate: coarse = 80:20), and the yaks were further prepared for a 21-day feeding trial, and rumen fluid samples were collected and compared by 16s rRNA sequencing. The results showed that NH3-N, Total VFA, Acetate, Butyrate, Isobutyrate and Isovalerate were significantly higher in the HC group than in the LC group (P<0.05), while microbial diversity and richness were significantly lower in the HC group (P<0.05). Principal coordinate analysis showed that rumen microflora was significantly different between LC and HC groups (P<0.05). In the rumen, Firmicutes and Bacteroidota were the most abundant bacteria at the phylum level, with Firmicutes being more abundant in the HC than in the LC group and Bacteroidota being less abundant in the HC than in the LC group. Christensenellaceae_R-7_group and Prevotella had the highest abundance at the genus level. The relative abundance of Acetitomaculum, Ruminococcus and Candidatus_Saccharimonas were significantly higher in the HC than in the LC group (P < 0.05), while the relative abundance of Olsenella was significantly lower in the HC group than in the LC group (P < 0.05). The relative abundance of Prevotella, Ruminococcus and Candidatus_Saccharimonas was significantly higher in the HC group than in the LC group. The relative abundance of Prevotella, Prevotellaceae_UCG-003, Olsenella, Ruminococcus, Acetitomaculum, Candidatus_Saccharimonas and NK4A214_group were correlated with rumen fermentation parameters (P< 0.05). Furthermore, PICRUSt 2 estimation indicated that microbial genes associated with valine, leucine, and isoleucine biosynthesis were overexpressed in the rumen microflora of yaks in the HC group (P< 0.05). In conclusion, our results suggest that high concentrate diets affect the fermentation function and microflora composition of yak rumen. The present findings could help provide some new insights into the health of yaks under high concentrate feeding conditions and provide a reference for the short-term fattening industry of yaks.